2009
DOI: 10.1016/j.iac.2009.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Anaphylaxis

Abstract: The incidence of immune-mediated anaphylaxis during anesthesia ranges from 1 in 10,000 to 1 in 20,000. Neuromuscular blocking agents represent the most frequently involved substances, followed by latex and antibiotics, but every drug or substance used may be involved. Diagnosis relies on tryptase measurements at the time of the reaction and skin tests and specific IgE or basophil activation assays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
94
1
20

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(116 citation statements)
references
References 93 publications
1
94
1
20
Order By: Relevance
“…Ayrıca genetik faktörlerin de önemli olduğu bildirilmiştir. Tip 1 hipersensitivite reaksiyonunun tahmini görülme oranı tüm anestezi vakaları arasında 1:1250 ve 1:10000'dir (11). Çoğu serilerde, Tip 1 reaksiyonlar perioperatif süre içinde gözlenen tüm aşırı duyarlılık reaksiyonlarının en az %60'ını temsil eder.…”
Section: Olgu Sunumuunclassified
“…Ayrıca genetik faktörlerin de önemli olduğu bildirilmiştir. Tip 1 hipersensitivite reaksiyonunun tahmini görülme oranı tüm anestezi vakaları arasında 1:1250 ve 1:10000'dir (11). Çoğu serilerde, Tip 1 reaksiyonlar perioperatif süre içinde gözlenen tüm aşırı duyarlılık reaksiyonlarının en az %60'ını temsil eder.…”
Section: Olgu Sunumuunclassified
“…Brought to you by | MIT Libraries Authenticated Download Date | 5/11/18 8:50 PM lower (13). Sensitivity of skin tests might decrease over time, a phenomenon particularly relevant for antibiotics (14), thus false negative results might occur.…”
Section: Figure 2 Box-plot For Si Values (Stimulation Index) For Basmentioning
confidence: 99%
“…Anaphylactic shock is a rare (approximately one case in 10,000-20,000 procedures) but life-threatening complication of anesthesia. 1 In France, various epidemiological studies over the last three decades have shown that the most common causal agents of anaphylaxis are NMBs. 2 In the event of anaphylactic shock, epinephrine is the first-line therapy.…”
mentioning
confidence: 99%
“…In the case of a potentially fatal emergency situation such as anaphylactic shock, a controlled trial appears difficult to undertake, particularly as this event is rare. 1 Therefore, what value can we give to the various published case reports? It is probable that only cases with a positive outcome were submitted for publication.…”
mentioning
confidence: 99%
See 1 more Smart Citation